Injuries in elite road cyclists during competition in one UCI WorldTour season: a prospective epidemiological study of incidence and injury burden. Issue 2 (4th March 2023) - Edler, Christopher; Droste, Jan-Niklas; Anemüller, Ruben; Pietsch, Aki; Gebhardt, Matthias; Riepenhof, Helge
ABSTRACT: To measure and evaluate the extent and characteristics of accidents and injuries in professional cycling competitions at the elite level (UCI WorldTour 2019) during one complete season. Methods: Fifty-four male athletes from two different teams were involved. Accidents and injuries were recorded immediately after the incident by a team physician present at every race. Exposure, location, type and cause of injury have been recorded. Incidence was calculated. Severity was measured as a cumulative severity score and burden depicted in a risk matrix. Results: Total time of exposure was 12537 hours over 3524 athlete days and 544002 kilometers of racing. 98 accidents were recorded, with 83 leading to injury. The total number of recorded injuries was 193. Injury incidence for all injuries was 54, 8 (±SD 47, 7–62, 8) /1000 athlete days, 15, 4 (±SD 13, 4–17, 7) /1000 athlete hours and 35, 5 (±SD 30, 8–40, 8) /100.000 km raced. By far the most frequent types of injury were hematomas, contusions and bruising (n = 141, 73%) followed by lacerations (n = 22; 11, 4%). Most injuries affected the arm and elbow (n = 34, 17, 6%) followed by the shoulder and clavicle (n = 28, 14, 5%) and occurred with contact (79%). Fractures pose a high injury burden due to long time loss, whereas hematomas, contusions and bruising showed the highest incidence numbers but comparably less time loss. Conclusion: Road cyclists' injuries have been underestimated in previous studies. Hematomas, contusions and bruising pose the highest number of injuries with a broad degree of severity and range of injury burden. Fractures are less common but show the highest injury burden. The upper extremities are involved the most.